Penerapan Good Corporate Governance dalam Meningkatkan Kinerja Keuangan Perusahaan - Eva Naura Maharani; Afriansyah Mufthi Akbar; Jovita Lituhayu Maheswari; Suwarsit Suwarsit (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Globalization and rapid economic growth encourage companies to implement effective and sustainable management practices to remain competitive in a dynamic business environment. One strategic approach to improving company performance is good corporate governance (“GCG”) which is an important element in achieving sustainable growth and improving financial performance. The implementation of good GCG is believed to have a positive impact on the company's financial performance, through increased transparency and accountability, making it easier for stakeholders, including investors, to assess the health of a company. In Indonesia, the implementation of GCG is a major focus to increase public trust, especially after several cases of management failures that resulted in significant financial losses. The regulations implemented by the Financial Services Authority (“OJK”) aim to strengthen supervision so that companies comply with international standards. However, there are still challenges in implementing consistency across sectors. This study uses qualitative methods to understand in depth how the implementation of GCG affects a company's financial performance as well as its supporting and inhibiting factors. This research is expected to help companies in Indonesia in developing more effective strategies to achieve long-term business goals and create sustainable added value for all stakeholders.